2022
DOI: 10.21744/ijhms.v5n2.1902
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's perceptions of anemia and iron supplement consumption

Abstract: Anemia is a condition that is commonly indicated by low hemoglobin levels in the blood. This situation is proven by the lack of quality and quantity of red blood cells that consequently decrease the amount of oxygen transported into the tissue. The high incidence of anemia in pregnancy can cause high maternal mortality after childbirth resulting from pregnancy complications such as bleeding. A lot of research on the factors that influence anemia and the prevention of anemia during pregnancy has been conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Subsequently a comprehensive prespecified and peerreviewed protocol. 11 Outcomes clearly support strong positive relations between periodontal disease and these outcomes and were extremely consistent across systematic reviews with low risk of bias. For a number of outcomes, there was supplementary evidence from within reviews that higher-quality chief studies supported this link.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Subsequently a comprehensive prespecified and peerreviewed protocol. 11 Outcomes clearly support strong positive relations between periodontal disease and these outcomes and were extremely consistent across systematic reviews with low risk of bias. For a number of outcomes, there was supplementary evidence from within reviews that higher-quality chief studies supported this link.…”
Section: Discussionmentioning
confidence: 57%
“…[8][9][10] Dependent on the specific bacterial strain, P. gingivalis dental infection encourages preterm delivery and fetal growth restriction with abnormal placental vascularization in mice, P. gingivalis DNA in human chorionic villous tissue or amniotic fluid has been linked to recurrent early miscarriage or premature labor with preterm LBW, respectively. [6][7][8][9][10][11][12] Presence of P. gingivalis in the placenta or umbilical cord has been associated with preterm birth and preeclampsia. Published guidelines on oral health care during pregnancy note that it is an underdeveloped area and that the relevance of oral hygiene during pregnancy is insufficiently recognized by dental and obstetric health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…There were other reports highlighting the advantages of this method which are used to generate stabilized genes of the patient's hematopoietic stem cell (HSC) that lead to effective erythropoiesis and avoid the haemolytic anaemia in thalassemia patients thus there is no need for blood transfusions. Two main obstacles while implementing a secured and efficient gene therapy are by providing an adequate amount of HSC cells as well as ensuring a safe transduce of CD34+ HSCs cells among the different levels of gene therapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…as shown in Table (1) and From Figure (4), it was found that the Impact resistance of epoxy is low due to its fragility, but the values of the Impact strength increase after strengthening it with Iron filings because iron improves this resistance because it bears the bulk of the Impact energy applied to the composite material [27]. temperature as a result of the relaxation of the bonds between the molecules of the material and its sliding movement, which gives it the possibility of absorbing part of the energy that leads to an increase in the energy needed to break [28], as shown in Table ( Figure (5) Relationship between Impact strength and Temperatures ℃ (8, 25,55) before and after reinforcement…”
Section: Impact Strengthmentioning
confidence: 99%